IR, RU, PT, AND PD IN BASALTS AND KOMATIITES: NEW CONSTRAINTS FOR THE GEOCHEMICAL BEHAVIOR OF THE PLATINUM-GROUP ELEMENTS IN THE MANTLE - Rehkämper M.; Halliday A.N.; Lee D.C.; Fitton J.G.; Wieneke M.; Arndt N.T. (My University, 1999)
The concentrations of the platinum-group elements (PGE) Ir, Ru, Pt, and Pd were determined in 18 mantle-derived basalts from a variety of tectonic settings and six komatiites from three locations. All analyses were performed using isotope dilution, Carius tube digestion, and the precise technique of multiple collector inductively coupled plasma mass spectrometry. Multiple analyses of two samples indicate external reproducibilities, based upon separate dissolutions, of approximately 2–9% in the ppt to ppb concentration range.